2007
DOI: 10.1038/sj.mt.6300262
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Gene Transfer Augments Angiogenesis in Ischemic Skeletal and Myocardial Muscle

Abstract: Urokinase plasminogen activator (uPA) is required for both endogenous and vascular endothelial growth factor (VEGF)-augmented angiogenesis in normal tissues, leading us to hypothesize that uPA augmentation by gene transfer might promote angiogenesis in ischemic tissues. Overexpression of uPA was studied in rat myocardial infarction (MI) and mouse hind limb ischemia models and compared with VEGF overexpression effects. Animals were divided into control and three experimental groups (n = 6), receiving intramuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 40 publications
1
25
0
4
Order By: Relevance
“…Consequently, VEGF, FGF2, and HGF induced PI3K-dependent activation of pro-uPA when bound to uPAR, and this led to an increase in cell surface fibrinolytic activity followed by uPAR internalization and redistribution [53]. uPA gene transfer effectively induces functionally significant angiogenesis in models of acute MI and hind limb ischemia [54]. Therefore, we can speculate that activation of the uPA system in ADSCs from older patients might be a compensatory response to the reduction of proangiogenic factor secretion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, VEGF, FGF2, and HGF induced PI3K-dependent activation of pro-uPA when bound to uPAR, and this led to an increase in cell surface fibrinolytic activity followed by uPAR internalization and redistribution [53]. uPA gene transfer effectively induces functionally significant angiogenesis in models of acute MI and hind limb ischemia [54]. Therefore, we can speculate that activation of the uPA system in ADSCs from older patients might be a compensatory response to the reduction of proangiogenic factor secretion.…”
Section: Discussionmentioning
confidence: 96%
“…Adipose tissue is an ideal source for MSCs because it is largely dispensable, and adipose-derived MSCs (ADSCs) are easily accessible in great amounts with minimal invasiveness compared with bone marrow-derived MSCs [1]. It was shown that local and systemic transplantation of ADSCs in animal models of hind limb ischemia and myocardial infarction (MI) led to an increase in the number of new blood vessels and improved blood perfusion within damaged tissue [2][3][4][5][6][7][8][9]. In attempts to explain the ability of ADSCs to stimulate angiogenesis, different mechanisms are considered.…”
Section: Introductionmentioning
confidence: 99%
“…повышение экспрессии урокиназы в эндотелиальных клетках увеличивает их ин-вазивный потенциал, а добавление антител, блокирующих урокиназный рецептор или про-теолитическую активность урокиназы, может подавлять миграцию эндотелиальных клеток и образование капилляроподобных структур [163,164]. Блокада урокиназного рецептора (uPar/cd87) с помощью специфических анти-тел подавляет индуцируемые фактором роста фибробластов (bfgf) и эндотелиальным фак-тором роста сосудов (Vegf) миграцию эндоте-лиальных клеток и образование капилляропо-добных трубочек в фибриновом матриксе [165].…”
Section: рис 11 механизмы регуляции роста и ремоделирования артерийunclassified
“…Мы изучали эффекты внутримиокарди-ального и внутримышечного введения плаз-мидной конструкции с комплиментарной Днк (кДнк) урокиназы (человека, крысы и мыши) на моделях ишемии задней конечности у мыши и крысы и инфаркта миокарда (иМ) у крысы [164,169]. Было показано, что урокиназа стимулирует развитие капилляров и артериол и увеличивает аккумуляцию макрофагов в пе-риинфарктной зоне, уменьшает размер форми-рующегося иМ, увеличивает васкуляризацию, ускоряет восстановление перфузии и предот-вращает развитие некроза в ишемизированной конечности (рис.…”
Section: рис 11 механизмы регуляции роста и ремоделирования артерийunclassified
“…HOXD3 has also been shown to have a role in vessel formation by endothelial cells through the activation of uPA transcription [100] . uPA is involved at all stages of angiogenesis, including endothelial cell division, migration, the formation of stable vessels, and the regulation of vascular permeability through proteolytic degradation of the extracellular matrix [102][103][104] . This is mediated through intracellular signaling initiated by its binding to receptors including uPA receptor (uPAR; CD87), low-density lipoprotein receptorrelated protein receptor (LRP/α2MR), and specific integrins [105][106][107][108][109][110] .…”
Section: Hox Transcription Factors and Angiogenesismentioning
confidence: 99%